KEILAHIAN YESUS MENURUT INJIL YOHANES - Supriadi Oet (Sekolah Tinggi Teologi Arastamar Bengkulu, 2016)
This paper wants to explain the Divinity of Jesus Christ according to the Gospel of John. This writing begins with the problematic present, namely the emergence of misconceptions about the person of Jesus Christ, such as the understanding of the Gnostic and pluralist groups today. To evaluate the wrong understanding needs a solid foundation, which is the gospel. The very gospel which deals with the person of Jesus Christ is the Gospel of John. With an explanation of the Divinity of Jesus Christ provides protection and answers to those who ask who Jesus Christ is.